2018
DOI: 10.7717/peerj.4572
|View full text |Cite
|
Sign up to set email alerts
|

Pollination implications of the diverse diet of tropical nectar-feeding bats roosting in an urban cave

Abstract: BackgroundIntense landscaping often alters the plant composition in urban areas. Knowing which plant species that pollinators are visiting in urban areas is necessary for understanding how landscaping impacts biodiversity and associated ecosystem services. The cave nectar bat, Eonycteris spelaea, is an important pollinator for many plants and is often recorded in human-dominated habitats. Previous studies of the diet of E. spelaea relied on morphological identification of pollen grains found in faeces and on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 62 publications
1
17
0
1
Order By: Relevance
“…However, it also appears that most of the bee diversity in cities is due to generalist bee species that have flexible diets and nesting habits, which stresses the importance of maintaining natural habitats for rare and specialist species. While we have less data on the effects of urbanization on vertebrate pollinators, the few studies that exist also suggest that cities can support generalist species that are tolerant of human development and activity, if their dietary and nesting or roosting requirements are met (Pauw and Louw 2012;Lim et al 2018, Diniz et al 2019Maruyama et al 2019).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it also appears that most of the bee diversity in cities is due to generalist bee species that have flexible diets and nesting habits, which stresses the importance of maintaining natural habitats for rare and specialist species. While we have less data on the effects of urbanization on vertebrate pollinators, the few studies that exist also suggest that cities can support generalist species that are tolerant of human development and activity, if their dietary and nesting or roosting requirements are met (Pauw and Louw 2012;Lim et al 2018, Diniz et al 2019Maruyama et al 2019).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 97%
“…However, the lack of more studies clearly impairs any generalizations on how urbanization affects bat pollination, and relevant factors may include roost availability, and light pollution among others (Diniz et al 2019;Sritongchuay et al 2019). Roosting site availability may be especially relevant, as a study from Peninsular Malaysia found a diverse number of plant species associated with the cave nectar bat, Eonycteris spelaea (Pteropodidae), inhabiting an urban cave (Lim et al 2018). Another limiting factor may be the lack of nightblooming plant species in cities since urban landscaping tends to favor showy day-blooming species (Loram et al 2008).…”
Section: Birds Bats and Other Vertebratesmentioning
confidence: 99%
“…), Indian trumpet (Oroxylum indicum), kapok tree (Ceiba pentandra), bitter bean (Parkia speciosa), and mangrove apples (Sonneratia spp.) (Acharya et al, 2015;Bumrungsri et al, 2013;Lim et al, 2018;Nor Zalipah et al, 2016;Nuevo-Diego et al, 2019;Stewart & Dudash, 2017). Of these, durian was a vital cash crop for both countries.…”
Section: Introductionmentioning
confidence: 99%
“…According to Struebig et al (2010), Old World fruit bats exhibit dispersal capabilities and generalist feeding habits. Eonycteris spleae (Dobson, 1871), a long-tongued fruit bat that is widely distributed in Southeast Asia remains an important pollinator of commercial food crops such as durian (Lim, 2018). Acharya et al (2015) recorded that this species travelled a long distance to foraging areas with durian, moving one-way between flowering patches of durian.…”
Section: Introductionmentioning
confidence: 99%